Antibiotic sensitivity on pathogenic bacteria causing bacterial vaginosis - Shiwi Linggarjati; Dita Diana Parti; Elly Nurus Sakinah (Majalah Obstetri dan Ginekologi, 2021)
Objectives: To identify the sensitivity of antibiotics to pathogenic bacteria that cause Bacterial Vaginosis (BV).Materials and Methods: This type of research was an observational study with a sample of six specimens. The data were taken using primary data from patients who were swabbed in the vagina and then diagnosed BV with amsel criteria on vaginal secretion specimens carried out at Tanggul health center on January 23-February 23, 2020. The specimens were sent to Parahita Clinical Laboratory for bacterial identification and adjusted for sensitivity with CLSI using vitek 2 compact tool.Results: The results of this study identified the bacteria that caused bacterial vaginosis, the E. coli and K. pneumoniae with one sample of suspected ESBL. ESBL is a beta lactamase enzyme produced by bacteria and can induce bacterial resistance to penicillin, cephalosporin generation 1, 2, and 3. The types of bacteria found were E. coli and K. pneumoniae with high sensitivity antibiotics tested including piperacillin/tazobactam, ceftazidime, cefepime, ertapenem, meropenem, amikacin, gentamicin, tigecycline, and nitrofurantoin. Antibiotics with high levels of resistance tested against these bacteria included: ampicillin, amoxicillin, and ampicillin/sulbactam due to the mechanism of beta-lactam antibiotic resistance in the production of beta lactamase from bacteria.Conclusion: The type of bacteria found was E. coli and K. pneumoniae with high resistance levels in beta lactam antibiotics.